2020
DOI: 10.3390/cells9071685
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Function of the Gene Encoding the Histone Methyltransferase KMT2D Leads to Deregulation of Mitochondrial Respiration

Abstract: KMT2D encodes a methyltransferase responsible for histone 3 lysine 4 (H3K4) mono-/di-methylation, an epigenetic mark correlated with active transcription. Here, we tested the hypothesis that KMT2D pathogenic loss-of-function variants, which causes the Kabuki syndrome type 1, could affect the mitochondrial metabolic profile. By using Seahorse technology, we showed a significant reduction of the mitochondrial oxygen consumption rate as well as a reduction of the glycolytic flux in both Kmt2d knockout MEFs and sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…Interestingly, both MDM2 and TUBA1B have been associated with the DNA damage response 49,50 , a function also associated with KMT2D 20 . NDUFB5 encodes a subunit of complex I, which plays a role in oxidative phosphorylation 51,52 , a pathway known to be dysregulated in KMT2D-deficient lung adenocarcinomas and Kabuki syndrome patients 53,54 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, both MDM2 and TUBA1B have been associated with the DNA damage response 49,50 , a function also associated with KMT2D 20 . NDUFB5 encodes a subunit of complex I, which plays a role in oxidative phosphorylation 51,52 , a pathway known to be dysregulated in KMT2D-deficient lung adenocarcinomas and Kabuki syndrome patients 53,54 .…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, FBXW11 is part of an E3 ubiquitin ligase complex involved in ubiquitination and proteasomal degradation in tumorigenesis signalling pathways 65 and has been shown to co-purify with the polycomb repressive complex 2 (PRC2) members EED 66 , SUZ12, and EZH2 65 , which play an antagonistic role to COMPASS complex members by depositing the repressive histone modification mark H3K27me3 67 . TFB1M is a mitochondrial transcription specificity factor that maintains homeostasis of oxidative phosphorylation and glycolysis 68,69 , pathways that have been shown to be dysregulated in KMT2D-deficient lung cancers 53 , epithelial cells, and Kabuki Syndrome patients 54 . Notably, KMT2D-deficient lung cancer cells depend on proper glycolytic activities for survival 53 , which is compatible with the notion that loss of TFB1M may be lethal for KMT2D-deficient cells.…”
Section: Resultsmentioning
confidence: 99%
“…This finding is reinforced by a previous work on KMT2D, in which a positive regulation of the glutathione detoxification pathway was observed by KMT2D [ 102 ]. Additionally, it was recently found that loss of KMT2D leads to deregulation of mitochondrial respiration and enhanced generation of ROS levels [ 103 ]. There is a large body of evidence that cancer cells often dysregulate mitochondria and show elevated levels of ROS [ 104 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fuel capacity evaluates the ability of cells’ to use a fuel to meet basal energy requirements when oxidation of the other two substrates was blocked. Fuel flexibility reflects the cells’ ability to switch or compensate mitochondrial respiration from one substrate to another [ 41 ]. Our results indicated that cortical astrocytes are more dependent on glucose for fuel supply than cerebellar astrocytes, while cerebellar astrocytes are more flexible on different fuel and rely more on glutamine and fatty acid for mitochondrial respiration.…”
Section: Discussionmentioning
confidence: 99%